2003
DOI: 10.1161/01.res.0000092142.19896.d9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Calcium ATPase Overexpression in Arterial Smooth Muscle Increases Vasomotor Responsiveness and Blood Pressure

Abstract: Abstract-In vascular smooth muscle cells (SMCs), several mechanisms act in concert to regulate the intracellular calcium concentration [Ca 2ϩ ] i , which may in turn affect vascular tone. One such mechanism is the extrusion of Ca 2ϩ by the plasma membrane calcium ATPase (PMCA). To address, in particular, the role of the neuronal nitric oxide synthase (nNOS)-associating isoform PMCA4b in regulating vascular tone, a doxycycline-responsive transgene for human PMCA4b was overexpressed in arterial SMCs of mice. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
5
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 46 publications
4
72
5
1
Order By: Relevance
“…ATP2B1 regulates the homeostasis of cellular calcium ion levels, which is important in controlling vascular smooth muscle contraction and dilation. 13,14 However, it has been difficult to speculate the exact role of ATP2B1 in physiology because of the large number of isoforms and the multiplicity of interacting molecules. 15 Related to its role in blood pressure, it is not clear yet whether ATP2B1 directly regulates the contraction and dilation of vascular smooth muscle by pumping out intracellular Ca ++ or it indirectly regulates the blood pressure by transmitting signals from vascular endothelial cells into the vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…ATP2B1 regulates the homeostasis of cellular calcium ion levels, which is important in controlling vascular smooth muscle contraction and dilation. 13,14 However, it has been difficult to speculate the exact role of ATP2B1 in physiology because of the large number of isoforms and the multiplicity of interacting molecules. 15 Related to its role in blood pressure, it is not clear yet whether ATP2B1 directly regulates the contraction and dilation of vascular smooth muscle by pumping out intracellular Ca ++ or it indirectly regulates the blood pressure by transmitting signals from vascular endothelial cells into the vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of ATP2B1 involves the homeostasis of cellular calcium ion levels, which is known to control vascular smooth muscle contraction and dilation. 14,15 The SNP rs1378942 is located in the first intron of CSK (c-src tyrosine kinase) at chromosome position 15q23-25. Our results showed that rs1378942 is associated with SBP in both cohorts (meta-analysis, P ¼ 1.34 Â 10 À5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is based on the PDZ domains in PMCA4b which lead to a complex with nitric oxide synthase I in caveolae of vascular smooth muscle (Schuh et al, 2001). PMCA gene-altered mice to date include gene-targeted PMCA1 , PMCA4 Schuh et al, 2004) and mice expressing PMCA4 using smooth muscle specific promoters (Gros et al, 2003;Schuh et al, 2003). At the level of PMCA mRNA message in mouse aorta, PMCA1 is reported to be approximately twice that of PMCA4, which is reversed in the PMCA4 smooth muscle specific transgenic.…”
Section: Plasma Membrane Ca 2+ Pumpsmentioning
confidence: 99%